2006
DOI: 10.1111/j.1574-6968.1997.tb10452.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral bacteria inhibit Helicobacter pylori growth

Abstract: Various oral bacterial species were found to inhibit the growth of Helicobacter pylori strains. The growth inhibitory activities of most of these oral bacteria were adversely affected by heating at 80 degrees C for 60 min or by protease treatment, indicating that these bacteria produce bacteriocin-like inhibitory proteins against H. pylori strains. The antagonistic effects of oral bacteria against H. pylori may restrain colonization by this organism in the oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…41 The tendency to co-aggregate with F. nucleatum was also confirmed in another experiment. 42 In addition, it has been determined that P. gingivalis may also be involved in such interaction and that this is a fimbriae-dependent process. 42 On this basis, it can be concluded that the presence of H. pylori is strongly associated with the physiological functioning of these two bacterial species (F. nucleatum and P. gingivalis) within the dental plaque, and vice versa.…”
Section: Interactions Of Oral H Pylori With Microbial Fl Oramentioning
confidence: 99%
See 1 more Smart Citation
“…41 The tendency to co-aggregate with F. nucleatum was also confirmed in another experiment. 42 In addition, it has been determined that P. gingivalis may also be involved in such interaction and that this is a fimbriae-dependent process. 42 On this basis, it can be concluded that the presence of H. pylori is strongly associated with the physiological functioning of these two bacterial species (F. nucleatum and P. gingivalis) within the dental plaque, and vice versa.…”
Section: Interactions Of Oral H Pylori With Microbial Fl Oramentioning
confidence: 99%
“…It has been observed that such microorganisms have the ability to inhibit H. pylori growth in vitro. 42 Diffusible compounds secreted by Streptococcus mutans 46 and Streptococcus mitis 47 contribute to a dramatic decrease in H. pylori viability. However, microscopic observation has shown that this effect was caused by the conversion of H. pylori to nonculturable coccoid forms.…”
Section: Interactions Of Oral H Pylori With Microbial Fl Oramentioning
confidence: 99%
“…[10][11][12] The transient existence of H pylori in the oral cavity seems to be associated with H pylori colonization in the stomach, but it is not known whether this reflects exposure to H pylori via an oral route or the presence of gastroesophageal reflux and the origin of this bacterium from the gastric lesions. 10 Because the prevalence of H pylori is low and decreasing among Finnish children, 13 we studied children only from refugee families of African origin. Among African children living in Finland, H pylori infection is common, and 63% of the children with gastrointestinal symptoms are seropositive for H pylori.…”
Section: Commentmentioning
confidence: 99%
“…In addition, the antibacterial effects of other SCFAs produced by P. gingivalis or C. butyricum on H. pylori still remain to be determined. Ishihara et al (1997) found that P. gingivalis and F. nucleatum strongly coaggregated with H. pylori. This finding suggested that these resident oral bacteria might be effectively trapping newly transiting bacteria such as H. pylori in periodontal pockets of the oral cavity.…”
Section: Discussionmentioning
confidence: 97%